Faktor-Faktor yang Mempengaruhi Non-Performing Loan (NPL) pada Bank Konvensional yang Terdaftar di BEI - Desi Safitri; Muhammad Suparmoko; Ende Ende (Lembaga Pengembangan Kinerja Dosen, 2026)
Non-Performing Loan (NPL) is an important indicator in assessing bank credit quality, where a high NPL ratio indicates problematic credit risk that may affect a bank’s financial stability. Several internal factors are presumed to influence NPL levels, including Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Operating Expenses to Operating Income (BOPO). This study aims to analyze the factors affecting NPL during the 2021–2025 period. This research employed a quantitative approach using secondary data obtained from annual financial reports. The population consisted of 44 conventional banks listed on the Indonesia Stock Exchange (IDX), with purposive sampling resulting in 8 selected banks observed over five years, yielding a total of 40 observations. Data were analyzed using panel data model selection, classical assumption tests, and multiple linear regression with EViews 12. The results indicate that CAR and LDR have no significant partial effect on NPL, while BOPO has a positive and significant effect on NPL. Simultaneously, the three variables significantly affect NPL and explain 21% of its variation. A high BOPO ratio reflects operating expenses exceeding operating income, thereby limiting banks’ resources in conducting credit supervision and analysis. Therefore, banks are advised to prioritize operational efficiency to control problematic credit risk.